Assessment of psychometric properties of the Dari version of the Pittsburgh Sleep Quality Index (PSQI) among Afghans - Ahmad Neyazi; Bilal Ahmad Rahimi; Abdul Qadim Mohammadi; Mehrab Neyazi; Muhammad Ishaque Faizee; Mohammad Naeem Daulati; Nosaibah Razaqi; Habibah Afzali; Laila Qanawezi; Shararah Sarem; Saida Said (Discover Psychology)
Abstract Background Sleep helps in improving the functions of all systems of human body. Disturbance in sleep can cause immediate adverse effects on normal human physiologic functions. Main objective of this study was to explore the psychometric properties of the Dari version of the of Pittsburgh Sleep Quality Index (PSQI) among general adult population of Afghanistan. Methods This methodological study has been conducted during July to November 2023. Reliability and validity of PSQI were evaluated using Cronbach’s Alpha and confirmatory factor analysis, respectively. Pearson correlation analysis was conducted to assess the convergent validity of the components of PSQI, comparing results with those obtained from the DASS-21 subdomains. Results In this cross-sectional study, 965 Afghan adults were studied during five months of duration between July and November, 2023. Mean age of the study participants was 35.2 years. The prevalence of sleep disturbance was 44.6% (430/965). Among them, 59.3% (572/965) reported experiencing subjective sleep quality disturbances less than once a week, 36.2% (349/965) had sleep latency issues less than once a week, 17.6% (170/965) had sleep duration disruption once or twice a week, while 36.3% (350/965) had daytime dysfunction less than once a week. The Cronbach’s alpha coefficient for the seven-component scale was 0.677, indicating acceptable internal consistency. Substantial and statistically significant positive correlations were present among the component of PSQI subjective sleep quality and sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleeping medication, daytime dysfunction, DASS-Depression, DASS-Anxiety, and DASS-Stress. The overall PSQI exhibited favorable fit indices, supporting the proposed single-factor structure among adult Afghan population. Conclusion Prevalence of sleep disturbance was very high among adult population of Afghanistan. This study provided useful information that will help policy makers (such as ministry of public health as well as international donor agencies like WHO, USAID, and UNICEF) to design a better strategy to reduce the prevalence of sleep disturbance that affects health of the Afghan community at large.